(untitled) (European Journal of Pure and Applied Mathematics, 2009)
In this paper, we introduce a new class of functions which is defined by Dziok- Srivastava operator and obtain the subordination results for this class of functions. Some known and new results, which follow as special cases of our results, have also been mentioned.